The Methodology of UAETrans Civil Actions Law Concerning Tort: An Analytical Comparative Study in Islamic Jurisprudence - اللهيبي صالح أحمد (Journal of Legal Sciences, 2019)
This paper deals with the position of the UAE Civil Transactions Law No. 5 of 1985 on the harmful act and how it dealt with this subject, and we know that the direct historical source of the civil transactions law is the Jordanian Civil Code. Some texts are quoted literally from this law. The Jordanian civil law is clearly influenced by the jurisprudence of Hanafi and the jurisprudential jurisprudence, while the general orientation of the UAE legislator is to adopt the most appropriate solutions in the jurisprudence with the introduction of the Maliki and Hanbali and Hanafi and Shafei, in the absence of legislation to rule the matter, the authors of the law The United Arab Emirates have changed some of the texts passed on to the Jordanian, but they do not abide by the amendment of the subsequent texts which should be amended in accordance with the previous amendment. In this paper, we dealt with the issues that we find most important in relation to the harmful act of harm, direct initiator and the cause of harm. , The harmed gathering between the wergild and compensation, and the position of the Federal Supreme Court and the Court of Dubai discrimination of these topics, and then concluded from this study several results such as a conflict between the provisions of the law of civil transactions UAE, and the base if met direct initiator and the cause of the addition of the act to the direct without the culprit is the basis You need to modify and add a lot of situations that require adding the verb to the sub-direct cause.